P5.024 Use of Rapid HIV Test in Low Threshold Centre in Antwerp, Belgium During 2007–2012. (13th July 2013) - Wouters, K; Fransen, K; Beelaert, G; Kenyon, C; Ghyseghem, C Van; Collier, I; Florence, E
Abstract : Introduction: Helpcenter (HC) is a low threshold centre for HIV and STI testing and dedicated to high risk groups: men having sex with men (MSM) and migrants from high endemic regions. Rapid HIV tests (RT) are used at HC for HIV screening since June 2007. The aim of this work is to describe our experience with this testing strategy. Methods: retrospective analyse of all RT routinely performed at HC. Tests are performed on plasma using the Determine Combo ® HIV-1/2 Ag/Ab (Alere) test (4th generation). Determine ® HIV-1/2 (3th generation) has been used until May 2009. All reactive tests were confirmed using INNO-LIA HIVI/II Score ® . A validation study was performed on 310 samples at the beginning of the project Results: up to December 2012, 5053 RT have been performed in 3884 persons including 1207 MSM and 994 migrants. The mean age was 33 years. 79 tests were reactive, 4968 negative and six not interpretable, two at the beginning of the project (learning curve) and four due to inappropriate light in the testing room and uncontrolled room temperature. Nine reactive tests were not confirmed with antibody or antigen tests (false-positive rate: 11.3%). No false-negative results have been observed during the validation study. The prevalence of HIV was high among the risk groups: 2.9% of MSM and 3% of migrants tested were found hiv-positive. The availability of RT was an important reason to consult at HC, 66% of the respondents highlight it as motivation to consult at HC. RT is offered to each person consulting at HC, 90% of them accepted to undergo a RT as screening for HIV. Conclusion: the RT is well accepted in a dedicated testing centre. The overall prevalence of HIV infection was 1.8%, nearly double in the target groups. Data on linkage to care will be presented.